Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization